Against steady state - Garzanti, Eduardo; Sternai, Pietro (Geologos, 2022)
Nature is never at a steady state. Natural history is generated by ever-new and ever-interacting forces that produce continuous changes. At virtually all timescales, the geological record shows that these changes do not cancel each other out and, thus, that the steady state is utopic. However, we need a state of equilibrium as a starting point for modelling Nature, and the steady-state condition is widely used as a reference in idealisations aimed at understanding natural processes. The present contribution is meant as an epistemological note of caution − from Earth scientists to Earth scientists - aimed at discouraging the use of theoretical models as true evidence instead of terms of comparison.